Medical Image Security Based On Diffusion- Substitution Method (International Journal of Scientific Research and Management (IJSRM), 2016)
In modern applications pertaining to transmission and receiving of multimedia data, the demand for data privacy has never been more significant. Hence, encryption of data becomes very much essential. Many encryption algorithms had been proposed, however, algorithms with high security, good efficiency and high performance are the demands of today’s applications. The work proposed in this paper is a diffusion process involving position based transformation with respect to pixels in two stages of encryption. The first stage involves dividing the image into non-overlapping blocks for which the image size is decided by a key. The second stage involves pixel shuffling with a particular pattern within each block in an image. The encryption algorithm implemented in this paper also validates for colour images of RGB format.